Correlation between plasma concentrations of calcitonin gene related peptide and pulmonary pressure in patients with systemic sclerosis. Issue 3 (1st March 2002) - Bartosik, I; Eskilsson, J; Ekman, R; Åkesson, A; Scheja, A
Abstract : Objective: To examine plasma levels of calcitonin gene related peptide (p-CGRP) in patients with systemic sclerosis (SSc) and pulmonary hypertension (PH). Material and methods: Twenty nine patients with SSc, 10 with diffuse form, 18 with limited form and one with overlapping systemic lupus erythematosus were examined. Twelve patients displayed normal systolic pulmonary artery pressure (PAPsyst) ≤30 mm Hg and 17 increased PAPsyst >30 mm Hg. Eight patients had isolated PH without interstitial lung disease (ILD) and nine had PH and ILD (secondary PH). PAPsyst was measured non-invasively by Doppler cardiography. CGRP was determined by radioimmunoassay. Results: Patients with PH had higher p-CGRP than patients with normal pressure. A positive relation was found between p-CGRP and PAPsyst and between p-CGRP and erythrocyte sedimentation rate (ESR), particularly in patients with isolated PH. Conclusion: In patients with SSc p-CGRP correlates with pulmonary pressure and with ESR. Whether CGRP reflects disease activity or is released secondary to pulmonary vasoconstriction needs to be investigated further.